Kinetic parameters of Lactobacillus acidophilus growth in the lactic fermentation of non-centrifugal cane sugar agroindustry wastes - Gonzalez-del Rosario, Itzel; Hernández-Martínez, José Manuel; Bolaños-Reynoso, Eusebio; Rosas-Mendoza, Erik Samuel; Méndez-Contreras, Juan Manuel (Renewable Energy, Biomass & Sustainability, 2024)
The use of sugarcane for the production of non-centrifugal cane sugar is one of the main economic activities in some areas of the central region of the state of Veracruz, México, however, this sector faces different social, techno-economic and environmental challenges. One of the most important problems affecting this agribusiness is the lack of adequate management of the waste generated in the process, mainly sugarcane scum (SCS) and mold wash water (MWW). Lactic fermentation is proposed as an alternative for the utilization of these wastes, since this process reduces the concentration of carbohydrates, producing lactic acid (LA) and increasing the nutrient content. An important aspect of the fermentation process is the knowledge of the kinetic parameters, since with these it is possible to carry out the scaling up. In the present work, the lactic fermentation of SCS and MWW was studied using the bacterium Lactobacillus acidophilus and the kinetic parameters were obtained with the Gompertz model and the Logistic model. The physicochemical characterization of the residues was carried out and the parameters of substrate consumption, lactic acid production and cell density were evaluated during fermentation of a 150 g SCS/L solution in a 0.5 L reactor. After 72 h of fermentation, a maximum growth of 7.63 log CFU/mL, a 50.32% carbohydrate consumption, and a maximum production of 7.56 g LA/L were obtained. For the Gompertz model, the parameters obtained were μmax=1.2420 h-1, λ=20.46 h y A=7.585 log CFU/mL, whereas for the Logistic model they were μmax=0.3214 h-1, λ=25.39 h y A=7.584 log CFU/mL. It was observed that both residues promote the development of the microorganism L. acidophilus, however, the kinetic parameters of μmax y λ indicates that it needs more time to adapt to the residues, so it will be necessary to implement strategies to optimize these values.